Plant-Based Cheeses: A Systematic Review of Sensory Evaluation Studies and Strategies to Increase Consumer Acceptance - Erin C. Short; Amanda J. Kinchla; Alissa A. Nolden (Foods, 2021)
Animal protein provides unique sensory and textural properties to foods that are not easily replicated when replaced with plant-based alternatives. Food scientists and researchers are currently developing innovative approaches to improve their physical and sensory characteristics in plant-based analogs. In terms of plant-based cheese substitutes (PBCS), soy is the most commonly used plant-based protein but is associated with undesirable sensory attributes (i.e., beany and gritty). In order to determine if the approaches result in a significant improvement in sensory quality and liking, sensory evaluation is employed. The aim of this review is to summarize the original literature (n = 12) relating to 100% PBCS which utilizes sensory evaluation methods. Overall, a major theme identified in this review is the innovative strategies used to increase acceptance of PBCS, whether products are aimed at improving existing non-dairy-based cheese formulations or to more closely mimic a conventional dairy-based cheese product. Studies demonstrate processing and fermentation of soybeans and blending of non-dairy milks are potential ways to improve consumer liking of PBCS. A secondary focus is to discuss the current sensory methodology carried out in the reviewed literature. Future studies should consider using more specific measures of flavor and mouthfeel, integrate evaluation of consumer liking with instrumental textural methods, and use a larger more diverse group of consumers. The outcome of this review is to highlight the importance of integrating sensory science in order to help facilitate the improvement of the sensory and quality attributes of PBCS and streamline product development.